Pengaruh Kompetensi Pegawai, Pemanfaatan Sistem Informasi Akuntansi, Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan - nuriasa, erva (Jurnal Riset Mahasiswa Akuntansi, 2024)
The purpose of this study was to determine the extent to which personnel skills, information technology utilization, and internal control affect the quality of business financial reports. The dependent variable of this study is the quality of financial statements, while the independent factors include staff competence, the use of accounting information systems, and internal control systems. The research subjects are employees of Orchadz Hotel in Pontianak City. Primary data in the form of qualitative data is used in this kind of research. Researchers use purposive sampling technique where the sample character is determined by the researcher where the sample understands and is related to financial reporting, treasury, accounting and finance such as admin-admin, and accounting staff. The number of respondents in this study amounted to 36. In this study, the analysis was carried out by multiple linear regression using the IBS SPSS 25 program. The results show that employee capabilities, the use of accounting information systems, and internal control improve the quality of financial statements.